Study of Potential of Polyethylene Foam as Sound Insulation for HVAC Rectangular Duct - Sulaiman, Muhammad Syahir; WAN ABDUL RAHMAN, WAN MOHD WARDI (Progress in Engineering Application and Technology, 2021)
Air conditioning system is very important in a building to distribute airflow with comfortable and quality. In the buildings, ventilation contributes to unwanted noise as the result of the interaction between the outlet air flow and the ventilation fins structure. The noise is caused due to design defect of air duct and it’s also possible defect from supply unit. In order to ensure a comfortable living and working environment, it is important to reduce the noise generated by air duct flow. This air duct is equipped with insulation made of fiberglass rather than to overcome this noise problem. In this study, polyethylene foam was used to replace the origin insulation that were presented by glass wool. A study has been conducted on polyethylene foam and glass wool to determine the level of efficiency in solving this noise problem. Two methods were performed in this study that is sound absorption coefficient and sound transmission loss and two devices were used that is impedance tube and reverberation chamber to complete this both experiments. Two thicknesses on both materials were used that is 12 mm and 25 mm as observations in this study. Overall, Findings from this experiment indicate that glass wool has a higher level as sound insulator than polyethylene foam. The thickness level of these two materials also greatly influenced the experimental results when it showed better results for the higher thickness